The impact of stalking and harassment in females of intimate partner violence in Johannesburg following the breakup of a relationship - Du Toit, Marlene (University of the Witwatersrand, Johannesburg, 2024)
Stalking and harassment should be considered a gender-based violence crime. Literature suggests that stalking and harassment often occur post-breakup of a relationship. It is often difficult to prove that a person is being stalked and harassed, hence the lack of legal avenues to protect oneself from stalking and harassment discussed herein. This research focused on stalking and harassment by a former intimate partner. The total number of participants was eight. The participants were recruited via Lifeline, an organisation that offers support to community members. Semi-structured interviews were conducted. The participants narrated their experiences and allowed the researcher to explore further during interviews. The interviews were recorded for analysis purposes. Thematic analysis was chosen as a method of analysis. Findings highlighted a form of abuse within the relationship that continued to evolve into stalking and harassment post the breakup. Former intimate partners sometimes used family members and friends to reach their victims. Technology was also used to reach the victims when unwanted visitation proved to be unsuccessful. Victims suffered psychological and physical distress due to stalking and harassment. Participants employed different coping mechanisms and used resources at their disposal, much outside of the judicial realm. There was a need expressed for the justice system to be more supportive and regard stalking and harassment seriously as a crime.
A research report Submitted in fulfillment of the requirements for a Master of Arts Clinical Psychology, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Harassment; former intimate partner; intimate partner violence; stalking; SDG-5: Gender equality